The Routledge handbook of philosophy, politics, and economics - Melenovsky, C. M. (Chris M.) (New York, NY : Routledge, 2022)
"This handbook advances the interdisciplinary field of Philosophy, Politics, and Economics (PPE) by identifying thirty-five topics of ongoing research. Instead of focusing on historically significant texts, it features experts talking about current debates. Individually, each chapter provides a resource for new research. Together, the chapters provide a thorough introduction to contemporary work in PPE, which makes it an ideal reader for a senior-year course. The handbook is organized into seven parts, each with its own introduction and five chapters: I.Frameworks II.Decision-Making III.Social Structures IV.Markets V.Economic Systems VI.Distributive Justice VII.Democracy The "Frameworks" part discusses common tools and perspectives in PPE, and the "Decision-making" section shows different approaches to the study of choice. From there, parts on "Social Structures," Markets" and "Economic Systems" each use tools from the three PPE disciplines to study and distinguish parts of society. The next part explains dominant theories and challenges to the paradigm of "Distributive Justice." Finally, a part on "Democracy" offers five challenges to current democratic practice"--
Introduction / C.M. Melenovsky -- PPE as an intellectual enterprise / Geoffrey Brennan and Geoffrey Sayre-McCord -- On models and their uses / James Johnson -- Complexity / Fred D'Agostino -- PPE in Marx's materialist conception of history / Vanessa Wills -- Feminist theory / Ann Cudd -- Game theory / John Thrasher -- Four structures of intransitive preferences / Luc Bovens -- Theories of choice behavior / Sudeep Bhatia -- Rule-following / Erik Kimbrough and Bart Wilson -- Implicit bias and decision-making / Lacey Davidson -- Social norms / Ryan Muldoon -- Institutions and institutionalism / C.M. Melenovsky -- Property / Bas van der Vossen -- Corporations in our polity / Amy Sepinwall -- Polycentricity / Vlad Tarko -- The advantages of markets / Matt Zwolinkski -- Exploitation / Vida Panitch -- The meaning of markets / Brookes Brown -- Gender and the division of labor / Gina Schouten -- Housing markets / Kristina Meshelski -- Capitalism / Peter Boettke -- Socialisms / Samuel Arnold -- Property owning democracy / Alan Thomas -- Social democracy / Jeppe Von Platz -- Corruption / Michael Munger -- Property rights and justice in holdings : a libertarian perspective / Erik Mack -- High liberalism / Samuel Freeman -- Institutionalism, injustice and personal responsibility / Kok-Chor Tan -- Social justice / Maeve McKeown -- Justice across borders / Serena Parekh -- In defense of epistocracy : enlightened preference voting / Jason Brennan -- Voting rules / Itai Sher -- Enabling informed and equal participation / Thomas Christiano -- What, if anything, can justify limiting workers' voice? / Liza Herzog -- Social trust / Karen Cook and Jacob Reidhead.
Includes bibliographical references and index.
Keywords: Political science -- Philosophy; Economics -- Philosophy; Social sciences -- Philosophy